Mussel mucin tissue adhesive as well as use method and application thereof

By employing a dual-channel chemical crosslinking and enzymatic secondary crosslinking synergistic design of mussel adhesive tissue binder, the issues of insufficient wet surface compatibility and biosafety in existing technologies have been resolved, achieving tissue bonding effects that are characterized by rapid curing, high strength, pressure resistance, washability, and good biosafety.

CN121287989AActive Publication Date: 2026-01-09BEOGENE BIOTECH GUANGZHOU
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511860926.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-11
Publication Date
2026-01-09
Estimated Expiration
2045-12-11

AI Technical Summary

Technical Problem

Existing tissue adhesives have problems such as insufficient wet surface compatibility, difficulty in balancing gelation speed and operability, insufficient strength and wash resistance, and trade-offs between biosafety and storage stability. They also have concerns about insufficient interfacial anchoring force, narrow operating window, and potential tissue irritation or residual reaction byproducts.

Method used

A two-component system of mussel adhesive tissue binder is adopted. Component A is PEG active ester, and component B is recombinant mussel adhesive protein and catechol grafted chitosan and transglutaminase. The active ester-amine rapid amidation achieves shaping and interfacial covalent anchoring. Subsequently, TGase forms ε-(γ-glutamyl)-lysine/γ-glutamyl-amine secondary crosslinking, which, combined with the catechin groups of MAPs-DOPA/CS-Cat, provides multi-point adhesion and energy dissipation on the wet surface.

Benefits of technology

It achieves rapid curing, high strength, pressure resistance, washability, good biocompatibility, strong storage stability, and user-friendly operation. It is also dimensionally stable in body fluids and has excellent sealing properties and promotes hemostasis and healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a mussel mucin tissue adhesive. The mussel mucin tissue adhesive has a two-component system with two-channel chemical crosslinking, enzymatic secondary crosslinking and catechol wet surface adhesion synergism, wherein a component A is PEG active ester, and a component B is recombinant mussel mucin (MAPs) and catechol grafted chitosan (CS-Cat) and is matched with transglutaminase (TGase). The preparation method comprises the following steps of: firstly, carrying out active ester-amine rapid amidation to realize sizing and interface covalent anchoring after mixing under the condition that the pH is approximately equal to 6.9, then forming epsilon-(gamma-glutamyl)-lysine / gamma-glutamyl-amine secondary cross-linking reinforcement by TGase, and meanwhile, providing wet surface multipoint adhesion and energy dissipation by catechol groups of MAPs-DOPA / CS-Cat. The cooperation mechanism faces the comprehensive target of rapid curing, high strength / pressure resistance, washing resistance and good compatibility and stability, and the key shortages in wet surface application in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of tissue adhesive, in particular to a mussel adhesive protein tissue adhesive and its use method and application. BACKGROUND

[0002] Medical tissue adhesive has become an important supplement to surgical suturing / nailing due to its advantages of simple operation, small trauma, instant sealing and hemostasis, and shortening of operation time. The adhesive usually forms a bond with the functional groups on the tissue surface through the reactive groups in the material under physiological conditions. Common reactive groups include: NHS / active carbonate (active ester), cyano acrylate, aldehyde group, catechol / ortho phenol, isocyanate, azide (click reaction), etc. In addition to covalent bonds, hydrogen bonds, hydrophobic interactions, electrostatic interactions, metal coordination and physical entanglement are also often used to improve the initial adhesion and overall bonding strength of wet surfaces.

[0003] According to the main components and curing mechanism, the existing tissue adhesives are roughly divided into four categories: (1) synthetic polymers: such as cyano acrylate, PEG system, polyurethane, polyester, etc., which rely on rapid polymerization or reaction with tissues to achieve curing; (2) proteins: such as fibrin glue, gelatin, albumin, etc., which rely on the coagulation cascade or chemical cross-linking to cure; (3) polysaccharides: such as chitosan, alginate, dextran, hyaluronic acid, etc., which often achieve curing through ion / physical or the introduction of reactive groups; (4) biomimetic adhesion: inspired by mussels, geckos, plant polyphenols, etc., using catechol groups to achieve adhesion on wet surfaces.

[0004] Among them, the most similar technical route to the present application is a two-component system composed of PEG active ester (such as PEG-NHS / PEG-SC) and protein (commonly albumin, gelatin, collagen, etc.): one side is active ester, the other side is amine-containing protein, after mixing, amide is formed to form a gel network, and some schemes are supplemented with physical thickening or surface activity to improve the adaptability of wet surface. A small number of documents have explored catechol-modified polymers or transglutaminase (TGase) for enhancing wet surface adhesion or secondary cross-linking, but most are single-channel improvements, and there is still a trade-off between gel speed, wet surface strength, resistance to washing, and storage stability.

[0005] Although the above systems have achieved certain applications, the following common problems still exist: (1) insufficient wet surface adaptability and unstable initial adhesion: most PEG-protein or polysaccharide systems mainly rely on single chemical cross-linking, and under the condition of continuous wetting and flushing of blood / body fluid, the interfacial anchoring force is insufficient, and adhesion failure or strength drop is easy to occur; (2) it is difficult to balance the gelation speed and operation window: although cyanoacrylate and the like have fast solidification, they are brittle, and the heat release and irritation limit their application in deep or large area wet surface; fibrin / gelatin has slow solidification and low strength, and the efficiency is limited during operation; (3) the strength and washing resistance are restricted by the cross-linking point density: in order to obtain a usable strength, PEG active ester-protein often needs a high solid content (such as ≥10-15% w / v), but this will increase the viscosity and reduce the injectability, and the NHS / SC end group is easy to hydrolyze and inactivate in aqueous solution, resulting in insufficient effective cross-linking points and increased batch difference; (4) single mechanism is difficult to meet the requirements of "sealing, pressure resistance and washing resistance" at the same time: the body phase network relying on chemical cross-linking often has insufficient sealing and burst pressure; the polysaccharide system relying on physical / ionic action has insufficient mechanical strength and stability; (5) compromise between biological safety and tissue compatibility: aldehyde / isocyanate has high reactivity, but has high risk of potential tissue irritation / cytotoxicity and residual reaction by-product; the brittleness and possible tissue irritation reaction of cyanoacrylate also limit its long-term application in some scenarios; (6) shelf life and on-site availability problems: the aqueous solution containing active ester has poor storage stability, and needs cold chain or present preparation and present use, which is difficult to balance long-term stability and rapid activation during operation; catechol materials are easy to self-oxidize and discolor in the presence of metal ions / oxygen, and the activity decreases, affecting the product performance; (7) lack of systematic design for synergistic solidification: most of the disclosed schemes are single channel (either chemical cross-linking, or biomimetic adhesion, or enzyme catalysis), and lack of systematic design for simultaneous optimization in three aspects of "rapid shaping + secondary reinforcement + wet surface anchoring" and precise synergy through A / B components and pH programming.

[0006] The existing tissue adhesives generally have the problems of insufficient wet surface adaptability, difficult balance between gelation speed and operability, insufficient strength and washing resistance, and compromise between biological safety and storage stability. For example: (1) when relying on single chemical cross-linking or physical action, the interfacial anchoring force is insufficient under the flushing of blood / body fluid, and adhesion failure is easy to occur; (2) in order to obtain a usable strength, a high solid content is often required, causing injection difficulty / operation window narrowing; active ester is easy to hydrolyze and inactivate in aqueous solution, and catechol is easy to self-oxidize and discolor, affecting the shelf life and use period performance; (3) some systems (such as cyanoacrylate, aldehyde / isocyanate cross-linking) may cause tissue irritation or residual reaction by-product concerns; (4) naturally derived proteins have batch difference and potential pathogen introduction risk, and still have insufficient wet surface strength and pressure sealing. SUMMARY

[0007] Based on this, it is necessary to overcome the shortcomings of the prior art, provide a mussel adhesive protein tissue adhesive, which has a two-component system of double-channel chemical cross-linking + enzymatic secondary cross-linking + catechol wet surface adhesion synergy: component A is PEG active ester (PEG-SS), component B is recombinant mussel adhesive protein (MAPs) and catechol grafted chitosan (CS-Cat) and transglutaminase (TGase). When the adhesive is used, components A and B are mixed, and under the condition of pH≈6.9, first, the active ester-amine rapid amidation realizes the setting and interface covalent anchoring, then TGase forms ε-(γ-glutamyl)-lysine / γ-glutamyl-amide secondary cross-linking reinforcement, and at the same time, the catechol groups of MAPs-DOPA / CS-Cat provide wet surface multi-point adhesion and energy dissipation. The synergistic mechanism faces the comprehensive goal of "fast curing + high strength / pressure resistance + resistance to washing + good compatibility and stability", and overcomes the key short board of the prior art in wet surface application.

[0008] The present application provides a mussel adhesive protein tissue adhesive, which is prepared from raw materials including component A and component B: the component A includes polyethylene glycol active ester, and the component B includes recombinant mussel adhesive protein, catechol grafted chitosan and transglutaminase; the recombinant mussel adhesive protein contains 3,4-dihydroxyphenylalanine (DOPA); In the raw materials, the polyethylene glycol active ester, the recombinant mussel adhesive protein, the catechol grafted chitosan and the transglutaminase are used in a ratio of (100-200) mg:(10-40) mg:(3-15) mg:(10-50) U.

[0009] In one embodiment, the polyethylene glycol active ester includes linear polyethylene glycol active ester or multi-arm polyethylene glycol active ester, and the deacetylation degree of the catechol grafted chitosan is 80-95%, and the catechol substitution degree is 5-15 mol%.

[0010] In one embodiment, the catechol grafted chitosan can be dissolved into a salt type to increase the solubility, and the salt type includes free amine, lactate, hydrochloride or carboxymethyl chitosan-Cat.

[0011] In one embodiment, the deacetylation degree of the catechol grafted chitosan is 90%, and the catechol substitution degree (DS) is 8-12 mol%.

[0012] In one embodiment, the molecular weight of the polyethylene glycol active ester is 5-40 kDa, and the molecular weight of the catechol grafted chitosan is 50-200 kDa.

[0013] In one embodiment, the polyethylene glycol active ester includes a four-arm polyethylene glycol active ester with a molecular weight of 10-20 kDa.

[0014] In one embodiment, the polyethylene glycol active ester includes a four-arm polyethylene glycol active ester with a molecular weight of 10 kDa.

[0015] In one embodiment, the catechol-grafted chitosan has a molecular weight of 100 kDa.

[0016] In one embodiment, the A component further includes a buffer and a lyoprotectant; the buffer of the A component includes 2-morpholinoethanesulfonic acid (MES), and the lyoprotectant of the A component includes trehalose and mannitol; the B component further includes sodium ascorbate, ethylenediaminetetraacetic acid disodium salt (EDTA-Na2), a buffer, and a lyoprotectant, the buffer of the B component includes 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) and sodium chloride, and the lyoprotectant of the B component includes trehalose and mannitol.

[0017] In one embodiment, the polyethylene glycol active ester end group includes N-hydroxysuccinimide (NHS) or succinimidyl carbonate (SC), which is linear or multi-armed and interchangeable, and the molecular weight is equally adjustable within 5-40 kDa to match the viscosity / strength.

[0018] In one embodiment, the catechol-grafted chitosan (CS-Cat) can be replaced by carboxymethyl chitosan-Cat.

[0019] In one embodiment, the catecholamine-based polymer group is provided by at least one of recombinant mussel myoglobin or catechol-grafted chitosan.

[0020] In one embodiment, the ascorbic acid can be replaced by or used together with glutathione, and the concentration of the glutathione is 1-2 mM.

[0021] In one embodiment, the ethylenediaminetetraacetic acid disodium salt can be replaced by diethylenetriamine pentaacetic acid pentasodium salt (DTPA·5Na), and the concentration of the diethylenetriamine pentaacetic acid pentasodium salt is 0.05-0.2 mM.

[0022] In one embodiment, the 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid can be replaced by phosphate buffered saline (PBS) or tris(hydroxymethyl)aminomethane (Tris).

[0023] In one embodiment, the lyoprotectant of the A component includes 50-100 mg of trehalose and 20-50 mg of mannitol, and the lyoprotectant of the B component includes 50-100 mg of trehalose and 20-50 mg of mannitol.

[0024] The application also provides a method for using the mussel adhesive protein tissue adhesive as described above, comprising the following steps: A component dissolving: taking the A component raw material, dissolving, mixing uniformly, and obtaining an A component solution; B component dissolving: taking the B component raw material, dissolving, mixing uniformly, and obtaining a B component solution; A, B component mixing: mixing the A and B component solutions uniformly, coating on the part to be adhered, and curing.

[0025] In one of the embodiments, the mass concentration of the polyethylene glycol active ester in the A component solution is 100-200 mg / mL; the mass concentration of the recombinant mussel adhesive protein in the B component solution is 10-40 mg / mL, the mass concentration of the catechol grafted chitosan is 3-15 mg / mL, the concentration of the transglutaminase is 10-50 U / mL, the concentration of the sodium ascorbate is 1-3 mM, and the concentration of the ethylenediaminetetraacetic acid disodium salt is 0.1-0.25 mM.

[0026] In one of the embodiments, the mass concentration of the polyethylene glycol active ester in the A component solution is 120-180 mg / mL; the mass concentration of the recombinant mussel adhesive protein in the B component solution is 20-30 mg / mL, the mass concentration of the catechol grafted chitosan is 4-8 mg / mL, the concentration of the transglutaminase is 30-40 U / mL, the concentration of the sodium ascorbate is 2 mM, and the concentration of the ethylenediaminetetraacetic acid disodium salt is 0.20 mM.

[0027] In one of the embodiments, the mass concentration of the polyethylene glycol active ester in the A component solution is 150 mg / mL, the mass concentration of the recombinant mussel adhesive protein in the B component solution is 12.5 mg / mL, the mass concentration of the catechol grafted chitosan is 4 mg / mL, and the concentration of the transglutaminase is 17.5 U / mL.

[0028] In one of the embodiments, the pH of the A component buffer after dissolving is 5-6; the pH of the B component buffer after dissolving is 7-8, and the pH of the mixture of the A and B components is 6.5-7.5.

[0029] In one of the embodiments, the concentration of the A component buffer after dissolving is 50-100 mM; the concentration of the 4-hydroxyethylpiperazine ethanesulfonic acid in the B component buffer after dissolving is 20-50 mM, and the concentration of the sodium chloride is 120-160 mM.

[0030] In one of the embodiments, the concentration of the sodium chloride in the B component buffer after dissolving is 150 mM.

[0031] In one of the embodiments, the pH of the A component buffer after dissolution is 5.3-5.5; the pH of the B component buffer after dissolution is 7.2-7.6, the pH of the mixture of the A and B components is 6.7-7.1, and the use environment temperature is 36-38℃.

[0032] In one of the embodiments, the pH of the A component buffer after dissolution is 5.4; the pH of the B component buffer after dissolution is 7.3-7.5, the pH of the mixture of the A and B components is 6.9, and the use environment temperature is 37℃.

[0033] In one of the embodiments, the pH of the B component buffer after dissolution is 7.4.

[0034] In one of the embodiments, in the mixing step of the A and B components, the volume ratio of the A component solution to the B component solution is 1:1; and the mixing mode is double syringe static mixing.

[0035] In one of the embodiments, the A component solution obtained after dissolution of the A component is 2mL; and the B component solution obtained after dissolution of the B component is 2mL.

[0036] In addition, the application also provides the use of the mussel myo-stromal adhesive or the mussel myo-stromal adhesive in the use method described above in the preparation of a medical tissue adhesive.

[0037] Compared with the prior art, the application has the following beneficial effects: (1) fast curing and good operation; (2) high strength adhesion of wet surface; (3) excellent sealing and pressure resistance; (4) strong resistance to washing and structure retention; (5) dimensional stability in body fluid; (6) hemostasis and healing promotion; (7) good biological safety; (8) advanced mechanism and clear synergy; (9) stable dosage form and clinical friendliness; (10) simplified system and strong expandability. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant embodiments. However, the present application can be realized in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thorough and comprehensive.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description of the application herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0040] Sources: The reagents, materials and equipment used in this example are commercially available sources unless otherwise specified; experimental methods are conventional experimental methods in the art unless otherwise specified.

[0041] Examples I. Composition and administration The mussel adhesive tissue adhesive of the embodiments of the present application is composed of two components: Component A is polyethylene glycol active ester (PEG-SS); Component B is recombinant mussel adhesive protein (MAPs), catechol grafted chitosan (CS-Cat) and transglutaminase (TGase), supplemented with sodium ascorbate and EDTA-Na2. The two components are freeze-dried in sterile vials, respectively, and before use, the matching reconstitution solutions are added for reconstitution, respectively, 2 mL of each is taken, and then the same volume is synchronously extruded and mixed through a double syringe and a static mixer, and then used.

[0042] II. Matching reconstitution solution (1) S-A (A bottle): the concentration of MES buffer is 50-100 mM, pH = 5.4; (2) S-B (B bottle): the concentration of HEPES buffer is 20-50 mM, containing NaCl at a concentration of 150 mM, pH = 7.4.

[0043] The pH of the system after mixing of A and B is about 6.9 (37°C).

[0044] III. Preparation of A / B components (freeze-dried powder) The present application also provides a preparation method of the freeze-dried powder of the A and B components, comprising the following steps: (1) Component A (PEG-SS freeze-dried powder): the target amount of four-arm PEG-SS (molecular weight 10000) is dissolved in S-A; 50-100 mg of trehalose and 20-50 mg of mannitol per bottle are added as freeze-drying protectants; the pH is adjusted to 5.3-5.5. The components are divided (the target volume for reconstitution of each bottle is 2 mL), pre-frozen at -40°C, gradient sublimation dried, and then stoppered and sealed, stored in the dark at 2-8°C.

[0045] (2) Component B (MAPs / CS-Cat / TGase freeze-dried powder): MAPs, CS-Cat and TGase are weighed and dissolved in S-B; sodium ascorbate (final concentration 2 mM) and EDTA-Na2 (final concentration 0.20 mM) are added; similarly, 50-100 mg of trehalose and 20-50 mg of mannitol per bottle are added; the pH is adjusted to 7.3-7.5. The components are divided, pre-frozen and freeze-dried under the same conditions as component A, and stored in the dark at 2-8°C.

[0046] IV. Use steps (1) Respectively add 2 mL of corresponding reconstituted solution (S-A / S-B) to A and B bottles, and shake gently until completely dissolved; (2) Load into double syringe and connect static mixer; (3) Apply evenly to the wound edge or sealing site, and fix with light pressure of 1-2 N, initial solidification for 90-120 s, and further strength increase for 5-15 min; (4) Intraoperative gentle flushing with normal saline can verify the adhesion stability.

[0047] After application, the A side formed by the A component is acidic, which helps to inhibit the hydrolysis of active ester, ensuring the reaction degree at the time of activation and the shelf life; the B side formed by the B component is nearly neutral, which maintains the nucleophilicity of amine and the activity of TGase; the CS-Cat provides a "amine + catechol" bifunctional site to enhance the initial adhesion of the wet surface and the bulk crosslinking.

[0048] Each of the following examples is based on "2 mL of reconstituted volume per bottle, A component:B component = 1:1 by volume".

[0049] Example 1 (standard type) (1) A component: four-arm PEG-SS (molecular weight 10000), concentration after dissolution 300 mg / 2 mL (S-A, pH=5.4; containing trehalose / mannitol).

[0050] (2) B component: MAPs, concentration after dissolution 25 mg / 2 mL, CS-Cat, concentration after dissolution 8 mg / 2 mL (deacetylation degree ≈90%, molecular weight ≈100 kDa, catechol substitution degree ≈10%), TGase, concentration after dissolution 35 U / 2 mL, containing sodium ascorbate (concentration 2 mM), EDTA-Na2 (concentration 0.20 mM) (S-B, pH=7.4; containing trehalose / mannitol).

[0051] (3) Use: mix equal volumes of A and B components, and quickly apply to the target site, and press with 1-2 N until solidification is complete.

[0052] Example 2 (enhanced catechol / initial adhesion) (1) A component: PEG-SS, concentration after dissolution 300 mg / 2 mL (S-A, pH=5.4).

[0053] (2) B component: MAPs, concentration after dissolution 25 mg / 2 mL, CS-Cat, concentration after dissolution 12 mg / 2 mL, TGase, concentration after dissolution 35 U / 2 mL, containing sodium ascorbate (concentration 2 mM), EDTA-Na2 (concentration 0.20 mM) (S-B, pH=7.4).

[0054] (3) The same as Example 1 was used.

[0055] Example 3 (High strength / rapid) (1) A component: PEG-SS, concentration after dissolution 360 mg / 2 mL (S-A, pH = 5.4).

[0056] (2) B component: MAPs, concentration after dissolution 30 mg / 2 mL, CS-Cat, concentration after dissolution 10 mg / 2 mL, TGase, concentration after dissolution 40 U / 2 mL, and containing sodium ascorbate (concentration 2 mM), EDTA-Na2 (concentration 0.20 mM) (S-B, pH = 7.4).

[0057] (3) The same as Example 1 was used.

[0058] Example 4 (Longer operating window / more flexible) (1) A component: PEG-SS, concentration after dissolution 240 mg / 2 mL (S-A, pH = 5.4).

[0059] (2) B component: MAPs, concentration after dissolution 20 mg / 2 mL, CS-Cat, concentration after dissolution 14 mg / 2 mL, TGase, concentration after dissolution 30 U / 2 mL, and containing sodium ascorbate (concentration 2 mM), EDTA-Na2 (concentration 0.20 mM) (S-B, pH = 7.4).

[0060] (3) The same as Example 1 was used.

[0061] Comparative Example 1 (No TGase) (1) A component: PEG-SS, concentration after dissolution 300 mg / 2 mL (S-A, pH = 5.4).

[0062] (2) B component: MAPs, concentration after dissolution 25 mg / 2 mL, CS-Cat, concentration after dissolution 8 mg / 2 mL, and no TGase was added; the rest was the same as Example 1 (S-B, pH = 7.4).

[0063] (3) The same as Example 1 was used.

[0064] Comparative Example 2 (Chitosan not grafted with pyrocatechol instead of CS-Cat) (1) A component: The same as Example 1.

[0065] (2) B component: MAPs, concentration after dissolution 25 mg / 2 mL, chitosan not grafted with pyrocatechol instead of CS-Cat, concentration after dissolution 8 mg / 2 mL, TGase, concentration after dissolution 35 U / 2 mL; the rest was the same as Example 1.

[0066] (3) The same as Example 1.

[0067] Comparative Example 3 (no MAPs, only CS-Cat participates) (1) A component: the same as Example 1.

[0068] (2) B component: MAPs, 10 mg / 2 mL after dissolution, CS-Cat, 6 mg / 2 mL after dissolution, TGase, 20 U / 2 mL after dissolution, and containing sodium ascorbate (2 mM), EDTA-Na2 (0.20 mM) (S-B, pH = 7.4).

[0069] (3) The same as Example 2.

[0070] Comparative Example 4 (low solid content) (1) A component: PEG-SS, 200 mg / 2 mL after dissolution (S-A, pH = 5.4).

[0071] (2) B component: MAPs, 10 mg / 2 mL after dissolution, CS-Cat, 6 mg / 2 mL after dissolution, TGase, 20 U / 2 mL after dissolution, and containing sodium ascorbate (2 mM), EDTA-Na2 (0.20 mM) (S-B, pH = 7.4).

[0072] (3) The same as Example 1.

[0073] Performance test 1. Gel time characterization Test method: According to the ratio in the implementation, the A component (four-arm PEG-SS, MES buffer pH = 5.4) and the B component (MAPs + CS-Cat + TGase, HEPES buffer pH = 7.4) were respectively reconstituted, mixed by equal volume through double syringe + static mixer, and then quickly added to the rotating rheometer loading table (37°C). The G′ / G″ curve with time was recorded at a fixed frequency / strain, and the intersection of the storage modulus G′ and the loss modulus G″ was defined as the gel point, and the corresponding time was the gel time (n = 5).

[0074] Table 1 Gel time

[0075] Results show that: The gel time of Examples 1-3 is significantly shorter than each of the comparative examples, reflecting the initial solidification advantage brought by PEG-SS rapid amidation + pH programming; among them, Example 3 (higher PEG-SS concentration, TGase concentration of 40 U / 2 mL) is the fastest. Example 4 (lower PEG-SS concentration, higher CS-Cat concentration) has a corresponding extended operation window. Comparative Example 1 (without TGase) and Comparative Example 2 (chitosan grafted with catechol instead of CS-Cat) both have delayed gelation, indicating that the formation of an enzymatic secondary network and the effective amine / catechol sites provided by CS-Cat can promote the early network building; Comparative Example 3 (without MAPs, only CS-Cat involved) is slower due to the lack of Gln / Lys corresponding sites at the end of the protein; Comparative Example 4 (low solid content) is the slowest, which is consistent with the expected lack of sufficient reactive site density.

[0076] 2. Lap-shear tensile strength Test method: According to "YY / T 0729.2-2009 Tissue Adhesive Bonding Performance Test Method Part 1: Lap-Shear Tensile Strength". Fresh pigskin was cut according to the standard size and moistened with PBS, and the A component (four-arm PEG-SS, MES buffer pH=5.4) and the B component (MAPs+CS-Cat+TGase, HEPES buffer pH=7.4) were respectively reconstituted according to the implementation, and then mixed with an equal volume of a double syringe and a static mixer, and then uniformly coated on the lap surface, and fixed with 1~2N pressure until solidification was completed. The test bar was clamped so that the stress direction was consistent with the long axis, and loaded at a speed of 5 mm / min until failure, and the failure load was recorded and converted to the bearing strength (n=6).

[0077] Table 2. Lap-shear tensile strength

[0078] Results show: (1) Examples 1-4 are significantly higher than the comparative examples, resulting from the rapid amidation of PEG-SS and MAPs / CS-Cat amine, plus TGase secondary crosslinking, and the catechol (MAPs-DOPA and CS-Cat) provides wet surface adhesion and interface anchoring.

[0079] (2) Example 3 is the highest, reflecting the synergistic enhancement of higher active ester / amine ratio + TGase (40 U / 2 mL).

[0080] (3) Comparative Example 1 (without TGase) significantly reduced strength due to lack of secondary isopeptide / γ-glutamyl- amide network; Comparative Example 2 (chitosan instead of CS-Cat without grafted catechol) limited interfacial adhesion and bulk crosslinking due to missing catechol sites and reduced amine site density; Comparative Example 3 (without MAPs, only CS-Cat involved) lacked Gln / Lys supply for protein side and TGase crosslinking was limited; Comparative Example 4 (low solid content) was the weakest due to insufficient crosslinking site density.

[0081] 3. T-peel strength Test method: Two fresh tissues (width noted as W) were taken and set with 25 mm overlap length. A and B components (four-arm PEG-SS in MES buffer pH=5.4 and MAPs+CS-Cat+TGase in HEPES buffer pH=7.4) were separately reconstituted and mixed by equal volume via double syringe and static mixer, then uniformly coated on the overlap area (wet glue amount about 0.15~0.20 g) and fixed by 1~2 N pressure until solidification (≥10 min). The two ends of the sample were clamped on the upper and lower clamps, respectively, and set at a peel angle of 180° (or 90°), with a crosshead speed of 50 mm / min, continuously peeled for ≥50 mm and the force-displacement curve was recorded. The average peel force F (N) was taken in the stable section, and the peel strength P=F / W (N / m) was calculated; the failure mode (adhesion / cohesion / substrate) was also recorded.

[0082] Failure mode determination index: Adhesion failure: occurred at the interface between the glue layer and the substrate; there was almost no residual glue on one side of the surface.

[0083] Cohesive failure: occurred within the glue layer; there was residual glue / filament on both sides of the surface.

[0084] Substrate failure: occurred in the tissue itself; the glue layer was still attached and the tissue was torn.

[0085] Mixed failure: two or more modes coexist in the same sample (reporting the percentage).

[0086] Table 3 Peel and failure mode evaluation

[0087] Results: Compared with the comparative examples, the peel strength of examples 1-4 is higher overall (about 320-410 N / m; example 3 is the highest), and the failure mode is changed from adhesion-based to cohesion-based with a small amount of substrate failure, showing that the interface bonding and gel network are more stable. Removing TGase (comparative example 1) significantly reduces the strength; replacing CS-Cat with ungrafted catechol chitosan (comparative example 2) limits both interfacial adhesion and bulk crosslinking due to the lack of catechol sites and the decrease in effective amine density; without MAPs, only CS-Cat is involved (comparative example 3), which lacks the enzymatic crosslinking sites provided by the protein side Gln / Lys, and the strength is frustrated; low solid content (comparative example 4) performs the worst due to insufficient crosslinking site density. The results show that the present application relies on PEG-SS rapid amidation + TGase secondary crosslinking and superimposes MAPs and CS-Cat catechol wet surface adhesion to significantly improve wet surface peel resistance and interface stability.

[0088] 4. Wound closure strength (wound edge approximation) Test method: Take the pig mesentery and cut it into 20 mm x 60 mm strip samples; cut a 20 mm standard slit in the middle of the sample. According to the implementation, respectively, dissolve component A (four-arm PEG-SS, MES buffer pH=5.4) and component B (MAPs+CS-Cat+TGase, HEPES buffer pH=7.4), mix equal volumes with a double syringe and a static mixer, then evenly apply glue (coating width 5-8 mm) along the wound edge, press and fix with 1-2 N pressure, and cure for 10-15 min. Clamp the two ends of the sample on the universal testing machine clamp, ensuring that the slit is in the middle of the clamp; stretch to failure at a crosshead speed of 5 mm / min, record the maximum load F_max (N) and displacement (mm). Calculate the closure strength σ=F_max / adhesive width (kPa). At the same time, record the failure mode (adhesion / cohesion / substrate or mixed).

[0089] Table 4 Wound closure strength

[0090] Results: The closure strength and displacement at break of Examples 1-4 were significantly higher than those of the comparative examples (about 85-120 kPa vs 30-52 kPa; 3.0-3.2 mm vs 1.7-2.2 mm), and the failure mode changed from adhesion in the comparative examples to mainly cohesion, and even cohesive→substrate failure in Example 3, indicating that the interface was stronger than the bulk. Removing TGase (Comparative Example 1) significantly reduced the strength; replacing CS-Cat with ungrafted catechol chitosan (Comparative Example 2) limited both interface anchoring and bulk crosslinking due to the lack of catechol sites and the decrease in effective amine density; only CS-Cat was involved without MAPs (Comparative Example 3), which lacked the enzymatic crosslinking sites provided by the Gln / Lys on the protein side, resulting in a decrease in strength; and low solid content (Comparative Example 4) was the worst due to insufficient crosslinking site density. In summary, the synergistic mechanism of "active ester fast crosslinking + TGase secondary crosslinking + catechol wet surface adhesion" in the present application can significantly improve the closure strength and toughness of the wound edge.

[0091] 5. Leak / burst pressure (sealing capacity) Experimental method: Take the isolated pig small intestine, and prepare a 2 mm diameter hole after unfolding; according to the implementation, respectively, dissolve the A component (four-arm PEG-SS, MES buffer pH=5.4) and the B component (MAPs+CS-Cat+TGase, HEPES buffer pH=7.4), mix equal volumes by double syringe+static mixer, and uniformly apply glue (cover about 12-15 mm in diameter) on the surface and surrounding area of the hole, and solidify for 10-15 min. Connect a constant flow pump and a pressure sensor, and increase the pressure at a rate of 10 mmHg / s, and record the first leakage pressure and the burst pressure (n≥5).

[0092] Table 5 Leak and burst pressures

[0093] The results show that: The leakage starting pressure and burst pressure of Examples 1-4 in the ex vivo small intestine model were significantly higher than those of each of the comparative examples (leakage of about 110-160 mmHg, burst of about 185-250 mmHg; control of 50-80 / 85-120 mmHg), of which Example 3 was the highest (160±16 / 250±20 mmHg), showing the best sealing and pressure resistance limit. Removal of TGase (Comparative Example 1) significantly reduced both indicators; substitution of CS-Cat with ungrafted catechol chitosan (Comparative Example 2) was insufficient in wet face anchoring and bulk crosslinking due to the absence of catechol sites and the reduction of effective amine density; no MAPs, only CS-Cat participation (Comparative Example 3) lacked the supply of protein side Gln / Lys to form an enzymatic crosslinking network, and the pressure resistance decreased; low solid content (Comparative Example 4) was the worst due to insufficient crosslinking point density. The results show that the present application relies on PEG-SS rapid film formation + sealing, TGase secondary covalent reinforcement, and the superposition of MAPs and CS-Cat catechol wet face adhesion, which can significantly improve the anti-leakage and pressure resistance of the perforated cavity tissue.

[0094] 6. Wash retention rate Experimental method: According to the "lap-shear" sample preparation process, respectively, reconstitute A component (four-arm PEG-SS, MES buffer pH=5.4) and B component (MAPs+CS-Cat+TGase, HEPES buffer pH=7.4), mix equal volumes by double syringe, coat and solidify. First measure the shear strength before washing; then place the sample in a 37°C constant temperature flow tank, under the action of circulating water, wash for 10 min, then retest the shear strength after washing. Calculate the retention rate: retention rate R=(strength after washing / strength before washing)×100%.

[0095] Table 6 Lap-shear tensile strength and retention rate before and after washing

[0096] Results show: Examples 1-4 still maintain higher lap shear strength and stability after rinsing, with retention rate of about 83~93% (of which Example 3 from 0.30→0.28 MPa, 93% best), significantly better than 50~64% of the comparative examples (and their initial strength is lower). Removal of TGase (Comparative Example 1) significantly reduces the retention rate; substitution of CS-Cat with ungrafted catechol of chitosan (Comparative Example 2) weakens the ability to resist rinsing due to the lack of catechol sites and the decrease in effective amine density; no MAPs, only CS-Cat involved (Comparative Example 3) lacks the supply of Gln / Lys on the side of the protein, and the secondary cross-linking is insufficient; low solid content (Comparative Example 4) is the worst due to insufficient cross-linking point density. The results show that the catechol wet surface adhesion relying on PEG-SS fast amidation + TGase secondary covalent reinforcement and superposition of MAPs / CS-Cat can effectively resist rinsing dilution and shear flushing, maintain wet surface adhesion and structural integrity.

[0097] 7. Swelling rate in body fluid Experimental method: According to the operation steps of the present application, the A component (four-arm PEG-SS, MES buffer pH=5.4) and the B component (MAPs+CS-Cat+TGase, HEPES buffer pH=7.4) are mixed in equal volume, and after complete gelation at room temperature for 30 min, a round piece with a diameter of 10 mm and a thickness of 2 mm is cut, and the initial mass m0 is recorded. It is placed in physiological saline and shaken gently at 37°C for 48 h, then the surface moisture is wiped off after taking it out, and the wet mass mt is recorded, and the swelling rate is calculated: Swelling rate S=(mt-m0) / m0x100%; Table 7 Swelling rate of each component in physiological saline

[0098] Results show: The 48h swelling rate of Examples 1-4 is significantly lower than that of each comparative example, of which Example 3 is the lowest (120±10%), indicating that the multi-point sites provided by PEG-SS fast amidation + TGase secondary cross-linking and superposition of MAPs / CS-Cat form a more compact network, reduce water absorption and swelling, and improve size and mechanical stability. Without TGase (Comparative Example 1), the swelling is significantly increased due to the lack of secondary cross-linking of isopeptide / γ-glutamine; substitution of CS-Cat with ungrafted catechol of chitosan (Comparative Example 2) reduces the network density due to the lack of catechol sites and the decrease in effective amine density; no MAPs, only CS-Cat involved (Comparative Example 3) is limited by the insufficient supply of Gln / Lys on the side of the protein; low solid content (Comparative Example 4) has the lowest cross-linking point density and the largest swelling.

[0099] 8. Hemocompatibility and hemostatic performance Hemolysis experiment Experimental method: Take the same donor's anticoagulant whole blood (sodium citrate), prepare 2% red blood cell suspension (0.9% NaCl wash 3 times after preparation); the gel which has been completely solidified at 37℃ is immersed in 0.9% NaCl at a surface area / volume of 3 cm 2 / mL for 24 h to obtain the extract (and make a material blank to deduct the background), take 0.5 mL of the extract and 0.5 mL of the red blood cell suspension, mix well, and incubate at 37℃ for 60 min; centrifuge (1000g, 5 min) and take the supernatant to measure the absorbance at 540 nm, hemolysis rate = (OD test tube-OD negative control tube) / (OD positive control tube-OD negative control tube)% The negative control is normal saline, and the positive control is pure water.

[0100] Table 8 Hemolysis rate of each group

[0101] The results show that: The hemolysis rate of all groups is ≤5% threshold, showing good blood compatibility; the overall implementation example is lower than the comparative example, and example 3 is the lowest. Comparative examples 2 and 4 are slightly higher but still compliant, indicating that when there is no grafted chitosan substitution or insufficient solid content, the interaction between the extract and the red blood cell membrane is more obvious; under the conditions of neutral buffer, sufficient solidification, and low soluble substance precipitation, the overall blood compatibility of the present application is good.

[0102] Whole blood clotting index (WBCI) experimental method: Place the pre-warmed 37℃ sample disc at the bottom of the transparent well plate (PBS wash 3 times, remove the free liquid), add 200 μL of sodium citrate anticoagulant whole blood and 20 μL of 0.2M CaCl2 to each well to start recalcification, incubate until the preset time point (5 / 10 / 20 min), then quickly add 2.0 mL of deionized water and gently shake for 3 min to dissolve the red blood cells not embedded in the clot, and take the supernatant to measure the absorbance at 540 nm; calculate the WBCI (%) based on the blank well (no sample surface), and the lower the value, the more sufficient the coagulation at that time point (the less residual soluble hemoglobin).

[0103] Table 9 Whole blood clotting index of each group

[0104] The results show that: The WBCI of examples 1-4 at each time point of 5 / 10 / 20 min is significantly lower than that of the comparative example (p<0.05), and example 3 is the lowest, and at 10~20 min it has approached the "sufficient coagulation" platform. The reasons are: 1. PEG-SS rapid amidation forms a dense barrier and fixes the wound edge; 2. TGase secondary crosslinking makes the gel network continue to densify within a few minutes, improving the resistance to seepage and shear; 3. The catechol groups of MAPs and CS-Cat are beneficial to adsorb fibrinogen / plasma proteins and promote platelet adhesion and embolus stability, thus accelerating clot formation and red blood cell entrapment.

[0105] Without TGase (Comparative Example 1) or replacing CS-Cat with non-grafted catechol chitosan (Comparative Example 2), the secondary crosslinking and catechol interface interaction are insufficient, and the WBCI is significantly higher; without MAPs and only CS-Cat participating (Comparative Example 3), the clot density is reduced due to the lack of enzymatic crosslinking sites provided by the protein side Gln / Lys; low solid content (Comparative Example 4) is the worst due to insufficient crosslinking site density. The results are consistent with the trends of the aforementioned closure strength, leakage / burst resistance, and washout retention rate, further verifying the synergistic hemostasis and sealing mechanism of the present application “active ester fast setting + TGase reinforcement + catechol wet surface anchoring”.

[0106] 9. In vitro cytotoxicity test Test method: According to “GB / T16886.5-2017 Medical Devices Biological Evaluation Part 5: In Vitro Cytotoxicity Test”. After the colloidal complete curing is prepared according to the implementation, the standard method is used to extract 24h with culture medium; the extracted liquid is used on L929 cells for 24h, and the absorbance is detected by CCK-8 method and the survival rate is converted. The normal cultured cells are used as control; if the survival rate is <70%, it is determined to have potential cytotoxicity (n=3).

[0107] Table 10 Potential cytotoxicity

[0108] Results: The cell survival rate of each group is ≥90%, and there is no potential cytotoxicity, which proves that the system of the present application has good cell compatibility.

[0109] 10. Irritation and skin sensitization test Test method: According to “GB / T16886.10-2017 Medical Devices Biological Evaluation Part 10: Irritation and Skin Sensitization Test”. Healthy New Zealand rabbits are selected; the back is shaved 10×15cm area as the contact and observation site. A / B colloids are prepared according to the implementation, mixed in equal volume, and then coated on a 2.5×2.5cm area until complete gel; after 4h of contact, remove with a wet gauze. Record the skin reaction and score at 1, 24, 48, 72h respectively.

[0110] Table 11 Skin reaction score and rabbit primary irritation index type

[0111] Results: All the examples and comparative examples have no skin sensitization reaction and good biological safety.

[0112] 11. Skin wound healing experiment Test method: Healthy SD rats were selected, and the back was shaved 4x6 cm as the observation area. After iodophor disinfection, a 2 cm full-thickness skin incision was prepared with a surgical blade. The A component (four-arm PEG-SS, MES buffer pH=5.4) and the B component (MAPs+CS-Cat+TGase, HEPES buffer pH=7.4) were respectively reconstituted according to the implementation mode, mixed in equal volume by double syringe, and then coated on the middle and periphery 2.5x0.5 cm area of the incision to form a complete gel; the complete closure time of the wound was recorded.

[0113] Table 12 Evaluation of adhesive on the healing time of rat wounds

[0114] The results show that: The healing time of examples 1-4 is shorter than that of the comparative examples (6-7 days vs 9-11 days), and example 3 is the fastest. The advantages come from the rapid amidation setting of PEG-SS and the secondary covalent reinforcement of TGase, and the superposition of MAPs and CS-Cat catechol wet surface adhesion, which can quickly and stably close, reduce leakage and micro-motion, thereby facilitating the formation of fibrin clot / fibrin network and early epithelialization. Without TGase (comparative example 1), the late strength is insufficient, and the closure maintenance is poor; replacing CS-Cat with ungrafted catechol chitosan (comparative example 2) lacks catechol sites and the effective amine density decreases, and the interface anchoring and bulk crosslinking are weakened; without MAPs and only CS-Cat involved (comparative example 3) lacks the enzyme crosslinking site of protein side Gln / Lys, and the stability is insufficient; low solid content (comparative example 4) is the slowest due to insufficient crosslinking site density. The overall results are consistent with the aforementioned trends of improved closure strength, leakage / burst resistance, and washing resistance.

[0115] The application provides a two-component medical tissue adhesive: the A component is polyethylene glycol active ester (PEG-SS), and the B component is recombinant mussel adhesive protein (MAPs) + catechol grafted chitosan (CS-Cat) + transglutaminase (TGase). The most preferred formula is as follows: the A component adopts four-arm PEG-SS (molecular weight 10000), the concentration is 150 mg / 2 mL, and the A component is reconstituted with MES (concentration 50 mM, pH 5.3-5.5); the B component is MAPs (concentration 25 mg / 2 mL), CS-Cat (concentration 8 mg / 2 mL, deacetylation degree approximately 90%, molecular weight approximately 100 kDa, catechol substitution degree approximately 10%), TGase (concentration 35 U / 2 mL), and contains sodium ascorbate (concentration 2 mM) and EDTA-Na2 (concentration 0.20 mM), and is reconstituted with HEPES (concentration 20-50 mM) + NaCl (concentration 150 mM), and the pH is 7.3-7.5; when used, the A component and the B component are each 2 mL in volume, and are sprayed out through a double syringe static mixer for use, and the pH of the system after mixing is approximately 6.9. Under the condition, a hierarchical network of 'fast setting + slow reinforcement + interface anchoring' is formed: within 1-3 min after mixing, the PEG-SS in the A component and the lysine epsilon-NH2 in the MAPs and the primary amine in the CS-Cat in the B component rapidly undergo amidation, an initial covalent network is established in the body phase, and interface covalent anchoring with histamine / thiol is realized (explain 90-120 s of initial solidification); subsequently, within 5-15 min, the TGase uses the glutamine (Gln) of the MAPs as an acyl donor to generate two types of secondary covalent cross-linking of epsilon-(gamma-glutamyl)-lysine (protein-protein) and gamma-glutamyl-amide (protein-glycosaminoglycan) with the lysine epsilon-NH2 of the MAPs or the primary amine of the CS-Cat, respectively, which significantly improves the cohesive strength and resistance to washing; at the same time, the DOPA of the MAPs and the catechol of the CS-Cat provide multiple-point hydrogen bond / hydrophobic-pi-pi / coordination non-covalent adhesion on the wet surface, and after mild oxidation into o-quinone, Schiff base / Michael addition and catechol-catechol coupling occur with histamine / thiol, further enhancing interface anchoring and energy dissipation. The ascorbic acid / EDTA in the formula inhibits catechol autoxidation and metal-induced side reactions, respectively, ensuring activity and color stability during storage and use; the four-arm PEG-SS (molecular weight 10 kDa, mass concentration 150 mg / 2 mL) balances the reaction rate, cross-linking point density and injection operability, the MAPs (mass concentration 25 mg / 2 mL) provide Gln / Lys and DOPA dual functional sites, the CS-Cat (mass concentration 8 mg / 2 mL) has both primary amine and catechol to compensate for the initial adhesion and coating on the wet surface under the condition of no rheological aid, and the TGase (concentration 35 U / 2 mL) covers the reinforcement window of 5-15 min during the operation.The above synergistic mechanism makes the present application have rapid gelation and high strength / washing resistance (for example, gelation / adhesion time of 90-120s, lap shear strength of 0.20-0.25MPa, closure strength of ≥90kPa, and washing retention rate of ≥80%) under physiological wet surface, and the rationality and feasibility thereof can be verified by the test results of the TGase-free, non-grafted chitosan, low solid content and SDS-PAGE / fluorescent receptor verification.

[0116] In summary, in view of the problems of the existing tissue adhesives, such as insufficient wet surface adaptability, difficult balance between gelation speed and operability, insufficient strength and washing resistance, and compromise between biological safety and storage stability, the present application solves the following problems: (1) rapid solidification and stable anchoring under physiological wet surface environment: initial solidification of 90-120s, maintaining interfacial bonding and shape stability under intraoperative washing / leakage conditions; (2) obtaining higher wet surface adhesion and bearing capacity: improving lap-shear strength, T-peel strength, wound edge closure strength and anti-leakage / burst pressure; (3) improving washing resistance and body fluid stability: maintaining high strength retention rate and low swelling under continuous washing and long-term soaking; (4) ensuring biological safety and compatibility: meeting medical requirements in hemolysis, cytotoxicity, stimulation / sensitization evaluation, and avoiding the risk of strong irritant / potentially toxic groups; (5) improving storage and on-site use stability: through A / B dual-vial lyophilization+pH programming, the activity of the active ester is preserved and the antioxidant effect of catechol is achieved, realizing ready-to-use and controllable operation window; (6) reducing the risk of raw material source and improving consistency: using recombinant mussel adhesive protein (MAPs) obtained by fermentation to replace natural extraction, reducing immunogenicity and pathogen-related risk, and using CS-Cat to provide controllable amine / catechol site density and rheological support.

[0117] The double-crosslinking tissue adhesive provided by the present application can be used for closing and sealing of soft tissues on the body surface / in vivo, hemostasis, anti-leakage / anti-burst, rapid plugging of cavity organs or blood vessel perforation, and tissue adhesion and wound edge approximation under wet surface environment. In addition, the present application has the following advantages: 1. fast solidification and good operation: after A / B equal-volume mixing, the initial solidification is completed in 90-120s (range of 80-165s in the examples), and 1-2N light pressure can be used for shaping, meeting the operation requirements of rapid leakage stopping / closing in surgery.

[0118] 2. high strength adhesion under wet surface: lap-shear strength of 0.24-0.30MPa, T-peel strength of 320-410N / m, failure mode changed from adhesion failure to mainly cohesion with a small amount of substrate failure, and more stable interfacial bonding and colloid network.

[0119] 3. Excellent sealing and pressure resistance: In the isolated small intestine perforation model, the initial leakage pressure is 110-160 mmHg and the burst pressure is 185-250 mmHg, which is significantly better than the control group (50-80 / 85-120 mmHg), suitable for sealing of cavity organ / vessel wound.

[0120] 4. Strong resistance to washing and structure retention: After 10 minutes of water washing at 37°C, the strength retention rate is 83-93% (control 50-64%), which can effectively resist surgical field washing and body fluid shear.

[0121] 5. Size stability in body fluids: The 48-hour physiological saline swelling rate is 120-180% (example) which is significantly lower than the control (170-224%), indicating that the cross-linked network is more compact and has better size and mechanical stability.

[0122] 6. Hemostasis and wound healing: The whole blood clotting index (WBCI) at 5 / 10 / 20 minutes is significantly lower than the control, indicating faster formation of a dense clot; the healing time of a 2 cm rat skin incision model is 6-7 days (control 9-11 days), indicating better early closure maintenance and tissue healing promotion.

[0123] 7. Good biological safety: Hemolysis rate ≤5%, no cytotoxicity, no irritation / sensitization in vitro; the buffer and ionic strength are close to physiological conditions, and the system is friendly.

[0124] 8. Advanced mechanism and clear synergy: Active ester-amine fast cross-linking (PEG-SS) + enzyme-mediated secondary cross-linking (TGase forms ε-(γ-glutamyl)-lysine / γ-glutamyl-amine) + catechol wet surface adhesion (MAPs-DOPA and CS-Cat) three-channel synergy, which not only ensures rapid shaping, but also provides post-reinforcement and interface anchoring.

[0125] 9. Stable dosage form, clinically friendly: A / B dual-vial lyophilization + differential pH reconstitution (A component: MES buffer pH=5.3-5.5; B component: HEPES buffer pH=7.3-7.5; mixed pH≈6.9) to balance storage stability, operation window and reaction efficiency; ascorbic acid / EDTA inhibits catechol non-controlled oxidation and metal-induced side reactions.

[0126] 10. System simplification and strong scalability: Without the use of tannic acid and γ-PGA, the above-mentioned performance is still achieved by relying on the "amine + catechol" dual function of CS-Cat; PEG active ester end group, CS-Cat salt type / substitution degree, molecular weight and concentration can be adjusted within a reasonable range, with potential for scale-up and scenario adaptation.

[0127] Any combination of the technical features in the above-described embodiments can be made, and for the sake of brevity, not all possible combinations are described, however, as long as the combination of the technical features does not exist in contradiction, it shall be considered within the scope of the present disclosure.

[0128] The above-described embodiments only express several implementation manners of the present application, and the description is relatively specific and detailed, but it shall not be understood as a limitation on the patent scope of the present application. It shall be pointed out that, for ordinary skilled persons in the art, several modifications and improvements can be made without departing from the concept of the present application, and these shall be within the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the appended claims.

Claims

1. A mussel myoglobin tissue adhesive, characterized in that, The preparation raw materials include A component and B component: the A component includes polyethylene glycol active ester, the B component includes recombinant mussel myoglobin, catechol grafted chitosan, transglutaminase; The recombinant mussel myoglobin contains 3,4-dihydroxyphenylalanine; In the preparation raw materials, the use amount ratio of polyethylene glycol active ester, recombinant mussel myoglobin, catechol grafted chitosan and transglutaminase is (100-200) mg:(10-40) mg:(3-15) mg:(10-50) U.

2. The mussel adhesive protein tissue adhesive according to claim 1, characterized in that, The polyethylene glycol active ester includes linear polyethylene glycol active ester or multi-arm polyethylene glycol active ester, and the deacetylation degree of the catechol grafted chitosan is 80-95%, and the catechol substitution degree is 5-15 mol%.

3. The mussel adhesive protein tissue adhesive according to claim 1, characterized in that, The molecular weight of the polyethylene glycol active ester is 5-40 kDa, and the molecular weight of the catechol grafted chitosan is 50-200 kDa.

4. The mussel myoglobin tissue adhesive according to any one of claims 1 to 3, characterized in that, The A component further includes a buffer and a freeze-drying protective agent; the buffer of the A component includes 2-morpholinoethanesulfonic acid, and the freeze-drying protective agent of the A component includes trehalose and mannitol; The B component further includes sodium ascorbate, ethylenediaminetetraacetic acid disodium salt, a buffer and a freeze-drying protective agent, the buffer of the B component includes 4-hydroxyethylpiperazine ethanesulfonic acid and sodium chloride, and the freeze-drying protective agent of the B component includes trehalose and mannitol.

5. The method of using the mussel adhesive protein tissue adhesive of claim 1, wherein, The method comprises the following steps: A component dissolution: taking the A component raw material, dissolving, mixing uniformly to obtain an A component solution; B component dissolution: taking the B component raw material, dissolving, mixing uniformly to obtain a B component solution; A, B component mixing: mixing the A component solution and the B component solution uniformly, coating on a part to be bonded, and solidifying.

6. The method of use of claim 5, wherein, In the A component solution, the mass concentration of the polyethylene glycol active ester is 100-200 mg / mL; In the B component solution, the mass concentration of the recombinant mussel myoglobin is 10-40 mg / mL, the mass concentration of the catechol grafted chitosan is 3-15 mg / mL, the concentration of the transglutaminase is 10-50 U / mL, the concentration of the sodium ascorbate is 1-3 mM, and the concentration of the ethylenediaminetetraacetic acid disodium salt is 0.1-0.25 mM.

7. The method of use of claim 5, wherein, In the A component solution, the mass concentration of the polyethylene glycol active ester is 120-180 mg / mL; In the B component solution, the mass concentration of the recombinant mussel myoglobin is 20-30 mg / mL, the mass concentration of the catechol grafted chitosan is 4-8 mg / mL, the concentration of the transglutaminase is 30-40 U / mL, the concentration of the sodium ascorbate is 2 mM, and the concentration of the ethylenediaminetetraacetic acid disodium salt is 0.20 mM.

8. The method of use of claim 5, wherein, The pH of the A component buffer after dissolution is 5-6; the pH of the B component buffer after dissolution is 7-8, and the pH of the mixture of the A component and the B component is 6.5-7.

5.

9. The method of use of claim 5, wherein, In the A, B component mixing step, the volume ratio of the A component solution to the B component solution is 1:

1.

10. The use of the mussel myoglobin tissue adhesive of claim 1 or the mussel myoglobin tissue adhesive in the use method of claim 5 in the preparation of a medical tissue adhesive.

Citation Information

Patent Citations

  • Medical tissue adhesive based on mussel mucin and hyaluronic acid and preparation method thereof

    CN115920117A

  • Tissue adhesive based on recombinant mussel mucin and application thereof

    CN117298326A

  • Mussel inspired nancomposite adhesives for biomedical applications

    US20210106718A1

  • Mussel-inspired tissue adhesives and methods of use thereof

    WO2024040270A2